Survey: IoT in Residential Areas for Energy Saving - Mochammad Haldi Widianto (Universitas Pendidikan Indonesia (UPI), 2022)
Internet of Things for House is an aspect that is desired by all industries or organizations. Making smart buildings is an important part of implementing smart concepts in various ways, now the need for energy savings is very high because the decline in the pandemic has made energy needs increase. Where all employers are applied Back to work in the office, making energy demands increase, especially in large industrial areas that require a lot of energy. One of the houses can take advantage of the Internet of Things (IoT). This technology can save energy by means of automation. In addition, there are several methodologies that can be used for energy efficiency, by utilizing sensors. This study uses a survey literature review to obtain research in the form of 20 papers to support research on smart housing.